PELAKSANAAN PENDIDIKAN LINGKUNGAN HIDUP BERBASIS KURIKULUM 2013 PADA USIA 5-6 TAHUN DI DANDELION DAYCARE (TAMAN PENITIPAN ANAK, KOTA DEPOK) - Rachmawaty, Mia (Jurnal Caksana : Pendidikan Anak Usia Dini, 2019)
Abstract: Environmental education is carried out in PAUD units by integrating into the 2013 PAUD curriculum with management standards starting from planning, implementation and supervision to further develop the needs and conformity of the vision and mission of the PAUD unit. This study seeks to reveal how the 2013 PAUD curriculum-based environmental education implementation in Daycare, Depok City. The approach taken in this research is qualitative with descriptive research type. Data collection is done by observation, interview and documentation techniques. Data processing uses qualitative data analysis stages, namely data reduction, data presentation and conclusion drawing. The results of the study illustrate that 1) the standard of environmental education management in planning criteria is quite good, but the supervision section should be carried out more intensively with a consistent schedule from the principal, so that the implementation criteria can optimally meet the needs of students. The structuring of the environment as part of the planning and design of the established curriculum has clearly seen its integration in the PAUD 2013 curriculum for the implementation of environmental education, 2) tangible manifestations of the implementation of environmental education can be seen in the design of daily activities that are applied consistently according to the draft concepts of environmental education materials and its development. Based on the conclusion of this research, the implementation of 2013 curriculum-based environmental education in Dandelion Daycare, Depok City is quite good.